Pedagogía y sexualidad - Margarita Elena Tapia Fonllem; Angélica de Guadalupe Terrazad Domínguez (iQuatro Editores, 2021)
Esta ponencia aborda la producción de conocimiento sobre sexualidad, surgida de las tesis de estudiantes de la Licenciatura en Pedagogía, de la Universidad Pedagógica Nacional, unidad Ajusco, de 1992 a 2018. El objetivo es conocer qué se ha investigado sobre la sexualidad, considerando: temas, niveles educativos, propuestas pedagógicas y temas emergentes. Se busca también actualizar programas de sexualidad y mejorar la asesoría al estudiantado en sus investigaciones sobre el tema. Abstract This paper contains accounts of knowledge production based on sexuality arising from pedagogy students' theses studying in the National Pedagogical University (Universidad Pedagógica Nacional-UPN), Ajusco Unit between 1992 to 2018. The objective is to become aware of what has been investigated on sexuality, considering topics such as educational levels, pedagogic proposals, and emerging issues. We also seek to make a proposal to update programs on sexuality and improve student counseling during their investigations on this subject. With the use of qualitative, exploratory and document analysis methodologies, 154 theses were found in which, the majority investigated middle school levels, focusing on sex education as the most analyzed.